Pengembangan Aplikasi Animasi Berbasis Kartun untuk Meningkatkan Pemahaman Geometri pada Siswa Sekolah Dasar - Kurniawan, Verina Deawany; Nurfitriani, Anita Rahayu; Setiyani, setiyani; Santi, Dina Pratiwi Dwi (Edumatica : Jurnal Pendidikan Matematika, 2025)
The conventional learning approach, which is less relevant to technological advancements, causes students to find it difficult to engage actively in the learning process, thereby limiting their understanding of the material. Sixth-grade students at a public elementary school in Cirebon City experience difficulties in comprehending spatial geometry concepts, such as the properties of three-dimensional shapes, volume calculation, and surface area. To address this issue, an animated cartoon-based spatial geometry learning application was developed to enhance students’ understanding interactively and enjoyably. The visually appealing element in the form of cartoon animation is expected to facilitate more concrete visualization of geometric concepts as well as increase students’ motivation to learn. This study employed a Research and Development (R&D) model using the ADDIE approach, which includes analysis, design, development, implementation, and evaluation stages. The material validation results obtained a score of 90.00%, while media validation scored 91.12%, both categorized as “highly feasible” for implementation. Testing with small and large groups also demonstrated very high results with percentages of 88.4% for small-scale testing and 90.1% for large-scale testing. This cartoon animation-based application can serve as an innovative alternative to support mathematics learning processes, particularly on spatial geometry topics, at the elementary school level.